The Impact of Economics on Contemporary Political Science - Miller, Gary J. (Journal of Economic Literature, 1997)
Early economic models assumed that the maximizing behavior of individual actors was the primary determinant of political as well as market outcomes. This approach revolved several long-standing puzzles in political science, but created new anomalies in place of the old: why do citizens vote in large elections? Why are democratic legislatures as stable as they are? Partly in response to these anomalies, the emphasis has shifted from the study of self-interested choice, to the study of constraints on self-interested choice. This has opened new doors for the study of bureaucracies, parties, and other fundamental political institutions.